Media Edukasi berbasis Smarphone: Aplikasi AECAS Edukasi Cegah Anak Stunting dalam Meningkatkan Pengetahuan Ibu - Studi Quasi Eksperimen Berbasis Komunitas - Fatimah, Fatimah; Astilia, Astilia; Andriyan, Aric Frendi (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: The problem of stunting, handling and prevention has become a global issue. Health problems against stunting have spread both through online and offline applications. However, the use of applications for stunting prevention efforts by increasing maternal knowledge has yet to be achieved, and some mothers' knowledge levels still need to be improved. Purpose: This study evaluates the use of the Prevention of Child Stunting Education Application (AECAS) to increase maternal knowledge in the Sijunjung Health Center Work Area, West Sumatra Province, Indonesia. Methods: A quasi-experiment with one group pre-test and post-test approach was used as the design of this study to measure participants' knowledge levels. They involved 31 participants, mothers whose children are stunted as an intervention group, who were given education about stunting prevention using the AECAS application available online. The AECAS application has passed the validity test. Data analysis used a paired T-test to test the significance level of pre-and post-test knowledge measurement. Results: 31 participants experienced increased knowledge from the sufficient category (mean score 54) to the good category (mean score 90). The statistical analysis results obtained the influence of participants' knowledge level before and after intervention with education on the use of AECAS applications (p-value = 0.001). They increased their knowledge score by 38. Conclusion: Using the AECAS application can increase mothers' knowledge about stunting and its prevention. Clinical nursing in the community can use the AECES application to increase knowledge, reduce the incidence of stunting and prevent stunting. Latar Belakang: Masalah stunting, penanganan dan pencegahan telah menjadi issue global. Promosi kesehatan tentang stunting telah menyebar baik melalui aplikasi online maupun offline. Namun, pemanfatan aplikasi untuk upaya pencegahan stunting dengan meningkatkan pengetahuan ibu belum merapa, sebagian tingkat pengetahuan ibu masih kurang. Tujuan: Studi ini berfokus untuk mengevaluasi pemanfaatan media Edukasi berbasis smarphone menggunakan aplikasi AECAS Edukasi Cegah Anak Stunting terhadap peningkatan pengetahun Ibu di Wilayah Kerja Puskesmas Sijunjung, Provinsi Sumatra Barat, Indonesia. Metode: Quasi eksperimen dengan pendekatan one group pre test dan post test digunakan sebagai design penelitian ini untuk mengukur tingkat pengetahuan partisipan.  Melibatkan 31 partisipan ibu-ibu yang anaknya stunting sebagai kelompok intervensi diberikan edukasi tentang penceghan stunting menggunakan aplikasi AECAS yang tersedia online. Apliaksi AECES telah lulus uji validitas. Analisis data untuk menguji tingkat kemaknaan pre dan post tets pengukuran pengetahuan digunakan paired T-test. Hasil: Partisipan berjumlah 31 mengalami peningkatan pengetahuan dari kategori cukup (skor mean 54) menjadi kategori baik (skor mean 90). Hasil analisis statistik diperoleh hasil ada pengaruh tingkat pengetahuan partisipan sebelum dan sedudah intervensi dengan edukasi pemanfataan apliaksi AECAS (p-value = 0,001). Peningkatan skor pengetahuan sebesar 38. Simpulan: Penggunaan aplikasi AECAS mampu meningkatkan pengetahuan ibu tentang stunting dan pencegahannya. Keperawatan klinis di komunitas dapat memanfaatkan aplikasi AECAS sebagai upaya peningkatan pengetahuan untuk menurunkan insiden stunting dan mencegah stunting.